EU MEMBERSHIP AND THE IMPACT ON THE IMAGE AND ATTRACTIVENESS ON TOURISM DESTINATIONS - Jorge Umbelino; José Miguel Rodríguez-Antón; Maria de la Soledad Celemín-Pedroche; Raúl Filipe; Éricka Amorim; Maria Adelaide Carranca (ENLIGHTENING TOURISM. A PATHMAKING JOURNAL, 2014)
The aim of this paper is twofold. Firstly, it aims to understand if the territory of the European Union (EU) contains any form of identity, with particular effects on tourism. Secondly, to identify how EU citizens interpret the Union in a special way when they choose their international tourist destinations. The key issue is to understand the behaviour of EU nationals as a new form of ‘domestic’ tourism in the European Union in order to know what factors determine the choice of an international tourism destination in Europe by European citizens and what attributes make a European tourist destination more attractive than other. That is why authors conducted a direct survey on EU residents. A descriptive and a factorial analysis have been applied to more than 600 replies received from 26 States.